Intubation biomechanics: laryngoscope force and cervical spine motion during intubation in cadavers-effect of severe distractive-flexion injury on C3-4 motion - Hindman, Bradley J; Fontes, Ricardo B; From, Robert P; Traynelis, Vincent C; Todd, Michael M; Puttlitz, Christian M; Santoni, Brandon G (Journal of neurosurgery. Spine, 2016)
OBJECTIVE With application of the forces of intubation, injured (unstable) cervical segments may move more than they normally do, which can result in spinal cord injury. The authors tested whether, during endotracheal intubation, intervertebral motion of an injured C3-4 cervical segment 1) is greater than that in the intact (stable) state and 2) differs when a high- or low-force laryngoscope is used. METHODS Fourteen cadavers underwent 3 intubations using force-sensing laryngoscopes while simultaneous cervical spine motion was recorded with lateral fluoroscopy. The first intubation was performed with an intact cervical spine and a conventional high-force line-of-sight Macintosh laryngoscope. After creation of a severe C3-4 distractive-flexion injury, 2 additional intubations were performed, one with the Macintosh laryngoscope and the other with a low-force indirect video laryngoscope (Airtraq), used in random order. RESULTS During Macintosh intubations, between the intact and the injured conditions, C3-4 extension (0.3° ± 3.0° vs 0.4° ± 2.7°, respectively; p = 0.9515) and anterior-posterior subluxation (-0.1 ± 0.4 mm vs -0.3 ± 0.6 mm, respectively; p = 0.2754) did not differ. During Macintosh and Airtraq intubations with an injured C3-4 segment, despite a large difference in applied force between the 2 laryngoscopes, segmental extension (0.4° ± 2.7° vs 0.3° ± 3.3°, respectively; p = 0.8077) and anterior-posterior subluxation (0.3 ± 0.6 mm vs 0.0 ± 0.7 mm, respectively; p = 0.3203) did not differ. CONCLUSIONS The authors' hypotheses regarding the relationship between laryngoscope force and the motion of an injured cervical segment were not confirmed. Motion-force relationships (biomechanics) of injured cervical intervertebral segments during endotracheal intubation in cadavers are not predicted by the in vitro biomechanical behavior of isolated cervical segments. With the limitations inherent to cadaveric studies, the results of this study suggest that not all forms of cervical spine injury are at risk for pathological motion and cervical cord injury during conventional high-force line-of-sight intubation.